2021
DOI: 10.21511/bbs.16(1).2021.07
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of cybercrime investigation in the banking sector of Ukraine: review and analysis

Abstract: The rapid growth in the number of cybercrimes committed in the banking sector requires the creation of an effective system for preventing such crimes and ensuring the cybersecurity of the state. The constant updating of means and methods for cybercrime commission necessitates the identification of effective measures to combat them. The paper uses a survey method to study the theoretical experience and practical measures to prevent cybercrime in the banking sector to identify effective ways to combat crime in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Bitcoin is a digital alternative to money, but despite its advantages, its active use is associated with risks to the financial system's stability and massive cyber fraud (Mnohoghitnei et al, 2022). Today, the level of cyber security in banking institutions does not meet their urgent needs to protect transactions; this is evidenced by the unsatisfactory level of their digitalization and the dependence of many systems and processes on human influence (Tran et al, 2022;Vitvitskiy et al, 2021). This can be a source of mass cybercrimes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bitcoin is a digital alternative to money, but despite its advantages, its active use is associated with risks to the financial system's stability and massive cyber fraud (Mnohoghitnei et al, 2022). Today, the level of cyber security in banking institutions does not meet their urgent needs to protect transactions; this is evidenced by the unsatisfactory level of their digitalization and the dependence of many systems and processes on human influence (Tran et al, 2022;Vitvitskiy et al, 2021). This can be a source of mass cybercrimes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the area of economic security, other views on threats to national security have gained ground, in particular due to the negative impact of the COVID-19 pandemic on national interests (Pidyukov et al, 2021) and qualified cybercrime in the financial, in particular, banking sphere (Vitvitskiy et al, 2021). The first one proposes to differentiate institutional, procedural and behavioral features, principles and indicators of the typology of challenges and threats caused by the crown virus pandemic in the world.…”
Section: The Essence and Manifestations Of National Security: A Scien...mentioning
confidence: 99%
“…8 No. 3, 2022 There are also separate studies in which certain factors of national security are revealed: the essence of migration as a prerequisite for ensuring national security and its legal regulation (Buhaichuk et al, 2021), cybercrime in the manifestation of the complex category "information terrorism" as one of the serious threats to national security (Varenia et al, 2021), the banking sphere as an environment for the development of cybercrime in its multifaceted nature (Vitvitskiy et al, 2021), the nature of economic security as the material basis of national security (Aleksandrova et al, 2021) and its international and national guarantees (Yarmol et al, 2021).…”
Section: Introductionmentioning
confidence: 99%